PENGARUH KONSENTRASI LARUTAN PEMUTIH H2O2 TERHADAP MUTU KERTAS BERBAHAN BAKU LIMBAH PADAT PELEPAH KELAPA SAWIT - Maulana, Adika Tito; Giyanto, Giyanto; Purjianto, Purjianto (Jurnal Agro Fabrica, 2023)
In general, solid waste from the palm oil industry contains high organic matter, which has an impact on environmental pollution. Improper handling of waste will pollute the environment. Various efforts have been made to process and increase the economic value of palm oil solid waste. Palm oil waste is the residue from the oil palm plant which is not included in the main product or is a by-product of the palm oil processing process, either in the form of solid waste or liquid waste. Oil palm solid waste can be in the form of empty fruit bunches, shells, bfiber and palm fronds. This research was carried out as an innovation from the previous research process with a differentiator, namely palm fronds, which in previous studies used empty palm oil bunches as raw material. In this study, hydrogen peroxide was used as a factor to determine the quality of paper made from palm fronds. Bleaching is a process of removing the color contained in the fiber due to the presence of lignin in the pulp with the help of chemicals. With three different concentration treatments aimed to determine the difference in the degree of whiteness, grammage and moisture content of the paper. Based on the results of the analysis of variance, it showed that the effect was significantly different on the concentration of the bleach solution (H2O2) with a variation of the concentration of 8% on the grammage with the highest grammage of 4% and 6% concentrations, and also had the lowest water content but at a concentration of (H2O2) 4% and 6% have higher water content.